2021
DOI: 10.1021/jacs.1c07139
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of (bi-Oxazoline)organonickel Complexes and Revision of a Catalytic Mechanism

Abstract: Bi-Oxazoline (biOx) has emerged as an effective ligand framework for promoting nickel-catalyzed cross-coupling, cross-electrophile coupling, and photoredox-nickel dual catalytic reactions. This report fills the knowledge gap of the organometallic reactivity of (biOx)Ni complexes, including catalyst reduction, oxidative electrophile activation, radical capture, and reductive elimination. The biOx ligand displays no redox activity in (biOx)Ni(I) complexes, in contrast to other chelating imine and oxazoline liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 49 publications
8
64
0
Order By: Relevance
“…The initial SET reduction of alkyl bromides by Ni(0) or Ni( i ) leads to alkyl radical I . 18,19 The resulting alkyl radical I is then trapped by 1,3-enyne to produce adduct radical II . At this stage, adduct radical II could be possibly intercepted by a low valent Ni( i ) compound to form the carbanion analogue.…”
mentioning
confidence: 99%
“…The initial SET reduction of alkyl bromides by Ni(0) or Ni( i ) leads to alkyl radical I . 18,19 The resulting alkyl radical I is then trapped by 1,3-enyne to produce adduct radical II . At this stage, adduct radical II could be possibly intercepted by a low valent Ni( i ) compound to form the carbanion analogue.…”
mentioning
confidence: 99%
“…The catalytic cycle begins with the active Ni­(I) species III , the generation of which accounts for the induction period. Two potential pathways, oxidative addition of alkenyl iodide to Ni­(I) III followed by Mn reduction of Ni­(III) or ejection of iodine radical, or bimolecular oxidative addition with III , afford (alkenyl)­Ni­(II) IV . While these two pathways are hardly to be distinguished at this stage, this oxidative addition step could be rate-determining in the transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these mechanistic studies and previous literature, we proposed a potential reaction pathway as shown in Scheme . Fluoroalkyl iodide is activated by [Ni]/Mn to form fluoroalkyl radical, followed by radical addition to alkene to generate alkyl radical I .…”
Section: Resultsmentioning
confidence: 99%
“…complexes are more resistant to reduction compared with the corresponding Ni(II) complexes of other commonly employed pyridyl-based ligands. 24 The presence of the phthalimido substituent in V and the interaction of V with the aldehyde and silyl chloride may affect the facility of this reduction by nanopowder zinc. Given these complexities, the precise nature of the conversion of V to II will require further investigation.…”
mentioning
confidence: 99%
“…The conversion of Ni­(II) complex V to the Ni­(II) silyloxyalkylnickel intermediate II requires a net two-electron reduction by zinc and oxidative addition of the aldehyde and silyl chloride. The commonly invoked reduction of nickel complex V to Ni(0) complex I completes the catalytic cycle, although this possibility must be viewed within the context of recent work from Diao et al that illustrates that Ni­(II) BiOx complexes are more resistant to reduction compared with the corresponding Ni­(II) complexes of other commonly employed pyridyl-based ligands . The presence of the phthalimido substituent in V and the interaction of V with the aldehyde and silyl chloride may affect the facility of this reduction by nanopowder zinc.…”
mentioning
confidence: 99%